Gas hydrate saturation from NGHP 02 LWD data in the Mahanadi Basin - Uma Shankar; Pradeep Kumar Yadav; Sneha Devi; Udham Singh Yadav (Energy Geoscience, 2024)
During the Indian National Gas Hydrate Program (NGHP) Expedition 02, Logging-while-drilling (LWD) logs were acquired at three sites (NGHP-02-11, NGHP-02-12, and NGHP-02-13) across the Mahanadi Basin in area A. We applied rock physics theory to available sonic velocity logs to know the distribution of gas hydrate at site NGHP-02-11 and NGHP-02-13. Rock physics modeling using sonic velocity at well location shows that gas hydrate is distributed mainly within the depth intervals of 150–265 m and 100–215 mbsf at site NGHP-02-11 and NGHP-02-13, respectively, with an average saturation of about 4% of the pore space and the maximum concentration of about 40% of the pore space at 250 m depth at site NGHP-02-11, and at site NGHP-02-13 an average saturation of about 2% of the pore space and the maximum concentration of about 20% of the pore space at 246 m depth, as gas hydrate is distributed mainly within 100–246 mbsf at this site. Saturation of gas hydrate estimated from the electrical resistivity method using density derived porosity and electrical resistivity logs from Archie's empirical formula shows high saturation compared to that from the sonic log. However, estimates of hydrate saturation based on sonic P-wave velocity may differ significantly from that based on resistivity, because gas and hydrate have higher resistivity than conductive pore fluid and sonic P-wave velocity shows strong effect on gas hydrate as a small amount of gas reduces the velocity significantly while increasing velocity due to the presence of hydrate. At site NGHP-02-11, gas hydrate saturation is in the range of 15%–30%, in two zones between 150-180 and 245–265 mbsf. Site NGHP-02-012 shows a gas hydrate saturation of 20%–30% in the zone between 100 and 207 mbsf. Site NGHP-02-13 shows a gas hydrate saturation up to 30% in the zone between 215 and 246 mbsf. Combined observations from rock physics modeling and Archie’s approximation show the gas hydrate concentrations are relatively low (<4% of the pore space) at the sites of the Mahanadi Basin in the turbidite channel system.